Testable Design for Positive Control Flipping Faults in Reversible Circuits - Mousum Handique; Hiren K D Sarma (IAES Indonesian Section, 2023)
Fast computational power is a major concern in every computing system. The advancement of the fabrication process in the present semiconductor technologies provides to accommodate millions of gates per chip and is also capable of reducing the size of the chips. Concurrently, the complex circuit design always leads to high power dissipation and increases the fault rates. Due to these difficulties, researchers explore the reversible logic circuit as an alternative way to implement the low-power circuit design. It is also widely applied in recent technology trends like quantum computing. Analyzing the correct functional behavior of these circuits is an essential requirement in the testing of the circuit. This paper presents a testable design for the k-CNOT based circuit capable of diagnosing the Positive Control Flipping Faults (PCFFs) in reversible circuits. The proposed work shows that generating a single test vector that applies to the constructed design circuit is sufficient for covering the PCFFs in the reversible circuit. Further, the parity-bit operations are augmented to the constructed testable circuit that produces the parity-test pattern to extract the faulty gate location of PCFFs. Various reversible benchmark circuits are used for evaluating the experimental results to establish the correctness of the proposed fault diagnosis technique. Also a comparative analysis is performed with the existing work.